Hypertension Treatment Effects on Orthostatic Hypotension and its Relationship with Cardiovascular Disease: Results from the AASK Trial - Juraschek, Stephen P. (Hypertension, 2018)
While orthostatic hypotension (OH) is often considered a contraindication to blood pressure (BP) treatment, evidence is lacking. We examined the effect of BP goal or initial medication choice on OH in AASK (African American Study of Kidney Disease), a 2×3 factorial trial. African Americans with chronic kidney disease (CKD) attributed to hypertension were randomly assigned one of two BP goals: intensive (mean arterial pressure [MAP]≤92mmHg) or standard (MAP 102–107mmHg), and one of three initial medications (ramipril, metoprolol, amlodipine). Postural changes in systolic BP (SBP), diastolic BP (DBP), or heart rate (HR) were determined after 2:45minutes of standing. OH was assessed each visit and defined using the consensus definition (drop in SBP≥20mmHg or DBP≥10mmHg). Median follow-up was 4-years. Outcomes were congestive heart failure, stroke, nonfatal cardiovascular disease (CVD), fatal CVD, any CVD (composite of preceding events), and all-cause mortality. There were 1,094 participants (mean age 54.5±10.7yrs; 38.8% female; OH was assessed at 52,864 visits). Mean seated SBP, DBP, and HR were 150.3±23.9mmHg, 95.5±14.2mmHg, and 72.0±12.6bpm. A more intensive BP goal did not alter the distributions of standing BP and was not associated with OH, but metoprolol was associated with systolic OH compared to ramipril (OR 1.68; 95%CI:1.15,2.46) and amlodipine (OR 1.94;95%CI:1.09,3.44). While consensus OH was associated with stroke (HR 5.01;95%CI:1.80,13.92), nonfatal CVD (HR 2.28;95%CI:1.21,4.30), and any CVD event (HR 2.12;95%CI:1.12,3.98), neither BP goal or medication altered this risk. Concerns about causing OH or its CVD consequences should not deter a lower BP goal among adults with CKD attributed to hypertension.